Jellyfish and other gelata as food for four penguin species – insights from predator‐borne videos. Issue 8 (5th September 2017) - Thiebot, Jean‐Baptiste; Arnould, John PY; Gómez‐Laich, Agustina; Ito, Kentaro; Kato, Akiko; Mattern, Thomas; Mitamura, Hiromichi; Noda, Takuji; Poupart, Timothée; Quintana, Flavio; Raclot, Thierry; Ropert‐Coudert, Yan; et al.
Abstract : Jellyfish and other pelagic gelatinous organisms ("gelata") are increasingly perceived as an important component of marine food webs but remain poorly understood. Their importance as prey in the oceans is extremely difficult to quantify due in part to methodological challenges in verifying predation on gelatinous structures. Miniaturized animal‐borne video data loggers now enable feeding events to be monitored from a predator's perspective. We gathered a substantial video dataset (over 350 hours of exploitable footage) from 106 individuals spanning four species of non‐gelatinous‐specialist predators (penguins), across regions of the southern oceans (areas south of 30°S). We documented nearly 200 cases of targeted attacks on carnivorous gelata by all four species, at all seven studied localities. Our findings emphasize that gelatinous organisms actually represent a widespread but currently under‐represented trophic link across the southern oceans, even for endothermic predators, which have high energetic demands. The use of modern technological tools, such as animal‐borne video data loggers, will help to correctly identify the ecological niche of gelata.